KADAR SERUM BESI PADA ANAK YANG TERINFEKSI SOIL TRANSMITTED HELMINTS DI DESA KUTAMBALIN KECAMATAN NAMAN TERAN SUMATERA UTARA - NUR FATIMAH; FANI ADE IRMA (LP2MTBM MAKARIOZ, 2022)
Worm disease is widespread, both in rural and urban areas. The infection rate is high, but the frequency of infection (number of worms in the stomach) is different. Indonesia ranks second in the Southeast Asian region for deworming treatment needs in children with a percentage of 15% after India is the first priority with a percentage of 61%. The negative impacts that can occur due to STH are declining health conditions, gastroenteritis, diarrhea, pneumonia, asthma, appendicitis, and malnutrition which can cause anemia, vitamin and iron deficiency, thereby inhibiting physical growth and development,Iron deficiency anemia can have an impact on physical growth, the development of brain intelligence, and increase the risk of decreased immunity which makes a person susceptible to infection. This study uses an observational research method with a cross sectional approach. The subjects in this study were the children of SD Negeri Kutambalin, Naman Teran sub-district, North Sumatra. With a sample of 16 children. Data analysis used fisher's exact test. From 16 samples, stool examination was performed using the diret slide method, it was found that 4 (25%) samples had STH infection and on blood examination 1 (6.25%) samples experienced a decrease in serum iron levels. Based on the results of this study, it was found that there was no decrease between serum iron levels in the blood and the incidence of STH infection